(untitled) (Psychology Travelogs, 2024)
The article presents the results of an empirical study of the characteristics of emotional intelligence in future psychologists. Particularly relevant are studies of emotional intelligence and personality traits that influence its changes during the study of young men in higher education institutions. It is proved that numerous studies deal with the phenomenon of emotional intelligence as an important characteristic affecting the professional activity of the individual and developing emotional intelligence in the learning process. The development of future psychologists’ emotional intelligence takes place in the process of both theoretical training (basic and specialised courses) and in the course of various practical tasks. As a result, both intrapersonal and interpersonal emotional intelligence develop, which provides the basis for successful professional activity in the future. The mixed two-component structure of emotional intelligence, which includes intrapersonal and interpersonal emotional intelligence, is empirically examined in this study. As students progress in their studies, there is a tendency for the level of emotional intelligence to increase. There is a decrease in the manifestation of emotional barriers in interpersonal communication: the dominance of negative emotions decreases, the desire to be closer to people on an emotional basis increases. There is an increase in the level of life satisfaction due to interest in life, consistency in achieving goals, consistency between set and achieved goals, positive evaluation of oneself and one’s actions, and a generally positive mood. There is a relationship between emotional intelligence, emotional barriers to communication, and life satisfaction among freshmen and emotional intelligence and emotional barriers to interpersonal communication among juniors and seniors.